Small for Gestational Age and Magnesium: Intrauterine magnesium deficiency may induce metabolic syndrome in later life - Junji Takaya (AIMS Press, 2015)
Magnesium deficiency during pregnancy as a result of insufficient or low intake of magnesium is common in developing and developed countries. Previous reports have shown that intracellular magnesium of cord blood platelets is lower among small for gestational age (SGA) groups than that of appropriate for gestational age (AGA) groups, suggesting that intrauterine magnesium deficiency may result in SGA. Additionally, the risk of adult-onset diseases such as insulin resistance syndrome is greater among children whose mothers were malnourished during pregnancy, and who consequently had a low birth weight. In a number of animal models, poor nutrition during pregnancy leads to offspring that exhibit pathophysiological changes similar to human diseases. The offspring of pregnant rats fed a magensium restricted diet have developed hypermethylation in the hepatic 11β-hydroxysteroid dehydrogenase-2 promoter. These findings indicate that maternal magnesium deficiencies during pregnancy influence regulation of non-imprinted genes by altering the epigenetic regulation of gene expression, thereby inducing different metabolic phenotypes. Magnesium deficiency during pregnancy may be responsible for not only maternal and fetal nutritional problems, but also lifelong consequences that affect the offspring throughout their life. Epidemiological, clinical, and basic research on the effects of magnesium deficiency now indicates underlying mechanisms, especially epigenetic processes.